The Natural Chemopreventive Agent Sulforaphane Inhibits STAT5 Activity - Pinz, Sophia (Public Library of Science, 2014)
Signal transducer and activator of transcription STAT5 is an essential mediator of cytokine, growth factor and hormone signaling. While its activity is tightly regulated in normal cells, its constitutive activation directly contributes to oncogenesis and is associated to a number of hematological and solid tumor cancers. We previously showed that deacetylase inhibitors can inhibit STAT5 transcriptional activity. We now investigated whether the dietary chemopreventive agent sulforaphane, known for its activity as deacetylase inhibitor, might also inhibit STAT5 activity and thus could act as a chemopreventive agent in STAT5-associated cancers. We describe here sulforaphane (SFN) as a novel STAT5 inhibitor. We showed that SFN, like the deacetylase inhibitor trichostatin A (TSA), can inhibit expression of STAT5 target genes in the B cell line Ba/F3, as well as in its transformed counterpart Ba/F3-1*6 and in the human leukemic cell line K562 both of which express a constitutively active form of STAT5. Similarly to TSA, SFN does not alter STAT5 initial activation by phosphorylation or binding to the promoter of specific target genes, in favor of a downstream transcriptional inhibitory effect. Chromatin immunoprecipitation assays revealed that, in contrast to TSA however, SFN only partially impaired the recruitment of RNA polymerase II at STAT5 target genes and did not alter histone H3 and H4 acetylation, suggesting an inhibitory mechanism distinct from that of TSA. Altogether, our data revealed that the natural compound sulforaphane can inhibit STAT5 downstream activity, and as such represents an attractive cancer chemoprotective agent targeting the STAT5 signaling pathway.